Economic Analysis of the Factors Affecting the Sheep Production: Case Study of Al-Hasaka District, Syria - Hammo, Alaa; Abdul-Aziz, Ali; Nasser, Shabab (Annals of Arid Zone, 2021)
Sheep rearing occupies an important role associated with animal production in Al-Hasaka governorate, due to the economic advantages it enjoys. Further, study of the production function is useful in measuring the production process and estimating the economic relations. These are important in determining the extent of production efficiency of the factors achievable that affects the sheep production. Accordingly, the research aimed mainly at measuring productive efficiency. The sample size was 313 rearers, who were chosen adopting a simple random sample method. The results identified the most influencing factors on the estimated production function. The sheep rearer experience and labor wage accounted for about 34% and 17%, respectively. Further, the use of production factors falls in the second stage of the production process, and the total flexibility reached was 1.479, and that the distribution efficiency of all factors of production was greater than one. The study recommends more efforts to increase investment in using factors of production to increase production to an level.Key words: Total production, return to scale, allocative efficiency, elasticity, sheep products.